Methodology of Using Digital Twin in Decision Making in Terms of Logistics Processes Automation - Michal ADAMCZAK; Adrianna TOBOLA (Communications of International Proceedings, 2021)
Background: The technological progress that we experience in many industries, as well as the need to quickly respond to changing customer needs, require logistic processes to respond equally fast or sometimes even faster to changing market conditions. The Industry 4.0 concept, providing modern techniques and tools, enables the use of a digital twin in the modeling and simulation of logistics processes, bringing the company not only financial benefits. Methods: The analysis of the literature was prepared in accordance with the PRISMA methodology based on the articles published in Web of Science and Scopus. In the part describing the author's methodology, the authors used the concept of digital twin and process automation. The methodology is supported by tools and techniques such as: business process modeling techniques (IDEF0, BPMN, Flow Chart, Data Flow Diagrams), process simulation, SCOR model, KPI, balanced score card, multi criteria decision making methods (point, weighted, graphical, indicator, Analytic Hierarchy Process). Results: The aim of this paper is to present an author's methodology for using digital twin to identification and verification of the effects of automation of logistics processes. The developed methodology is divided into three stages: analysis of the current process - developing a digital twin, definition of process automation variants, variant analysis based on the digital twin. Conclusions: The use of digital twin allows to support the decision-making process in the selection of variant of logistics process automation. In developing a digital twin, it is necessary to remember about the effectiveness of its use. Therefore, it should be a tool as simple as the purpose for which it was created allows. The choosing of an automation variant requires the determination of the effects of its implementation. Modeling and simulation of processes are perfect for this without generating high costs and high labor consumption.
Keywords: Business Process Modeling and Simulation; Logistics Process Automation; Digital Twin; Industry 4.0; Decision Making Process